PROSPECTS OF USING BY-PRODUCTS OF SUNFLOWER OIL PRODUCTION IN COMPOUND FEED INDUSTRY - B. Yegorov; Т. Turpurova; E. Sharabaeva; Y. Bondar (Harčova Nauka ì Tehnologìâ, 2019)
The article considers the possibility of obtaining a protein-rich feed additive from by-products of sunflower oil production. From literary sources it is known that in the global food market, Ukraine ranks first in cultivating the sunflower and in production and export of sunflower oil. Correspondingly, there are more by-products, such as press cakes and oil meal, which are high-protein feeds for farm animals. Recently, oil press factories have been producing high fat press cakes for farm animals and poultry’s energy needs. The shelf-life of high fat press cakes is very short, and besides, their physical properties are poor. So, it has been suggested to produce a protein-rich feed additive based on sunflower oil meal, sunflower press cake and limestone flour. The quality parameters of sunflower seeds and by-products of their processing have been determined. Five samples of the additive with different ratios of sunflower oil meal, sunflower press cakes, and limestone flour have been studied. The coefficient of variation characterizing the even distribution of the components in the additive has been determined. Besides the distribution of limestone flour in the additive, the distribution of sunflower press cake matter has been investigated, because it contains a lot of fat and has poor physical properties. The determination of the coefficients of variation by the distribution of limestone flour and by the distribution of sunflower press cake matter has shown that the mixing is the most effective when the recipe includes 75% of sunflower oil meal, 10 % of sunflower press cake, and 15% of limestone flour. A protein-rich feed additive based on by-products of the sunflower oil production has been developed. The additive can be used to feed animals and poultry.